OPTIMASI SPASIAL SEKTOR UNGGULAN PADA ANALISIS SEMI INPUT–OUTPUT: STUDI KASUS PROVINSI JAWA TIMUR - Yuliyanti, Rifa Diana; Koestoer, Raldi Hendro (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
East Java Province has a relatively complex region therefore challenges to promote and Encourage the regional economic growth are escalated. One of the technique to improve is through a search of their leading sector that reflects real effective and efficient robust export sector. Meanwhile, the distribution of the strongest tradable and export-led sector in provincial regional level remains limited for economic development study, this research attempts to explore it in provincial regional level for two periods of Input-Output (I-O) analysis.The research observed the movement of sector value from I-O analysis in 2006 tothe year 2010’s I-O analysis. Combination approach performed with I-O analysis that separates between the tradable and nontradable group of sectors formerly which is called Semi InputOutput. Followed by modification of ‘flow-on effects’multiplier and Location Quotient that represent the spatial dimension of the sector, the spatial–regional base distribution expresses subtly the result of the leading sector in defining natural resources capacity which is available through its distribution.Keywords : Spatial; Input-Output; Semi Input-Output; Location Quotient; Flow-on effects; Tradable